THE INFLUENCE OF TRUST SHARIA COMPLIANCE AND RISK PERCEPTION ON PURCHASE DECISIONS AT TIKTOK STORE - Astuti, Oktifindi Ira; Lisman, Muhammad (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
Based on data from the Association of Indonesian Internet Providers (APJJI) the number of people connected to the internet will reach 210,026,769 people out of a total population of 272,628,600 people in Indonesia in 2021. Among the popular app and business platforms is Tik Tok. It was recorded that from 2018 to 2022, TikTok users have increased by 490.4% with users in 2022 of 1.53 billion users. This study aims to determine the effect of trust, compliance and perceived risk on purchasing decisions in generation Z of 270 samples. The results of the study show that there is a partial influence of trust and sharia compliance on purchasing decisions at the Tiktok Shop. The next hypothesis states that there is no effect of perceived risk on purchasing decisions at the Tiktok Shop. The fourth hypothesis states that there is a simultaneous influence of trust, sharia compliance and perceived risk on purchasing decisions at the Tiktok Shop. The result of the coefficient of determination (R2) is 38.5%. This research has many drawbacks, therefore the recommends It is advisable for further researchers to expand the reach of the research area so that it can provide a variety of responses to researchers. Future research may consider using different data collection and data analysis methods.